Integration of Papuan Regional Songs as A Means of Cultural Preservation In Social Science Learning to Strengthen Students' Cultural Identity Class V C SD Hikmah 1 Yapis Jayapura Papua Province - Yusuf, Selvia; Handoko, Susanto T; Jamal, Ode (Universitas Nusantara PGRI Kediri, 2026)
This research aims to examine the integration of Papuan regional songs as a means of preserving culture in Social Sciences (IPS) learning in order to strengthen the cultural identity of class V students at SD Hikmah 1 YAPIS Jayapura. The background to this research is based on the importance of strengthening students' cultural identity from an early age and the limited use of Papuan regional songs as contextual and meaningful social studies learning media. This research uses a qualitative approach with a case study type of research. Research subjects included fifth grade social studies teachers, fifth grade students, school principals, Papuan cultural figures, and students' parents. Data collection techniques are carried out through observation, structured interviews, and documentation, while data analysis uses data reduction techniques, data presentation, and drawing conclusions. The research results show that the integration of Papuan regional songs in social studies learning is carried out through the planning and implementation stages of learning which link social studies material with local cultural values ​​contained in Papuan regional songs. The impact of integrating Papuan regional songs can be seen in increasing students' understanding of local social and cultural values, growing feelings of pride and love for Papuan culture, as well as strengthening students' cultural identity.